2004
DOI: 10.1093/nar/gki024
|View full text |Cite
|
Sign up to set email alerts
|

The CATH Domain Structure Database and related resources Gene3D and DHS provide comprehensive domain family information for genome analysis

Abstract: The CATH database of protein domain structures (http://www.biochem.ucl.ac.uk/bsm/cath/) currently contains 43 229 domains classified into 1467 superfamilies and 5107 sequence families. Each structural family is expanded with sequence relatives from GenBank and completed genomes, using a variety of efficient sequence search protocols and reliable thresholds. This extended CATH protein family database contains 616 470 domain sequences classified into 23 876 sequence families. This results in the significant expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
168
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(173 citation statements)
references
References 22 publications
3
168
0
1
Order By: Relevance
“…The β-subunit of the Na + -channel has an Ig-fold domain in the extracellular region and was demonstrated to be involved in cell-cell adhesion via a direct interaction with the extracellular matrix (Srinivasan et al, 1998;Undrovinas et al, 1995;Xiao et al, 1999). Recent bioinformatic analysis and x-ray crystallography demonstrated that the Ig-fold structure can be found in various proteins (Halaby et al, 1999;Pearl et al, 2005). Each Ig fold is composed of sequential and antiparallel short β-sheets, some of which are relatively hydrophobic (Halaby et al, 1999).…”
Section: Possible Involvement Of the β-Subunit In Cell-cell Adhesionmentioning
confidence: 99%
“…The β-subunit of the Na + -channel has an Ig-fold domain in the extracellular region and was demonstrated to be involved in cell-cell adhesion via a direct interaction with the extracellular matrix (Srinivasan et al, 1998;Undrovinas et al, 1995;Xiao et al, 1999). Recent bioinformatic analysis and x-ray crystallography demonstrated that the Ig-fold structure can be found in various proteins (Halaby et al, 1999;Pearl et al, 2005). Each Ig fold is composed of sequential and antiparallel short β-sheets, some of which are relatively hydrophobic (Halaby et al, 1999).…”
Section: Possible Involvement Of the β-Subunit In Cell-cell Adhesionmentioning
confidence: 99%
“…In spite of the low sequence identity, usually below 10%, PRYSPRY and the proteins of the top DALI hits share the same core b-sandwich architecture, that of a jelly roll topology (CATH, [31]). Interestingly, in pea lectin [30], a homologue of the CRD of p58/ERGIC-53, an extended binding pocket is located on the concave side of the b-sheet as we see in the PRYSPRY-domain (Fig.…”
Section: Fold Comparison With Other Proteinsmentioning
confidence: 99%
“…CATH server classified the protein as alpha beta with a 2-layer sandwich architecture and topology similar to double stranded RNA binding domain (Pearl et al, 2004). The overall structure consists of 3 helices and 3 sheets.…”
Section: Introductionmentioning
confidence: 99%